Active disturbance rejection control of three-phase LCL power conversion system under non-ideal grid conditions - Wang, Sue; Yang, Junbo (Frontiers in Energy Research, 2023)
Under the non-ideal grid operating conditions such as grid voltage is unbalanced and harmonic grid commonly found in microgrid conditions, the negative sequence components of the microgrid voltage interfere with the active and reactive current control in the Power Conversion System, leading to an increase in the harmonic content of the grid-side current and affecting the power quality of the microgrid system. To solve these problems, firstly, the mathematical model of LCL-type Power Conversion System is analyzed, and a linear active disturbance rejection controller based on model compensation is designed. Secondly, the influence of non-ideal power grid conditions on the control of LCL-type Power Conversion System is analyzed, and the active disturbance rejection control strategy of LCL type LCL-type Power Conversion System based on the generalized second-order integrator frequency locking loop is proposed, which speeds up the system, improves the system robustness, and reduces the harmonic content of network measurement current under the condition of power grid voltage imbalance and harmonic power grid. Finally, by the verification of Matlab/Simulink simulation, the current power quality obviously under the condition of voltage unbalance and harmonic power grid is evidently improved by the proposed control strategy.